A hundred suns : [large type] a novel - Tanabe, Karin (Thorndike Press, a part of Gale, a Cengage Company, 2020)
On a humid afternoon in 1933, American Jessie Lesage steps off a boat from Paris and onto the shores of Vietnam. Accompanying her French husband Victor, an heir to the Michelin rubber fortune, she's certain that their new life is full of promise, for while the rest of the world is sinking into economic depression, Indochine is gold for the Michelins. Jessie knows that their vast plantations near Saigon are the key to the family's prosperity, and while they have been marred in scandal, she needs them to succeed for her husband's sake--and to ensure that her trail of secrets stays hidden in the past. Jessie dives into the glamorous colonial world, where money is king and morals are brushed aside, and meets Marcelle de Fabry, a spellbinding French woman with a moneyed Indochinese lover, the silk tycoon Khoi Nguyen. Descending on Jessie's world like a hurricane, Marcelle proves to be an exuberant guide to ex-pat life. But hidden beneath her vivacious exterior is a fierce desire to put the colony back in the hands of its people, starting with the Michelin plantations, fueled by a terrible wrong committed against her and Khoi's loved ones in Paris. Yet it doesn't take long for the sun-drenched days and champagne-soaked nights to catch up with Jessie. With an increasingly fractured mind, her affection for Indochine falters. And as a fiery political struggle builds around her, Jessie begins to wonder what's real in a friendship that she suspects may be nothing but a house of cards.